Pengaruh Rata-Rata Lama Sekolah, Dana Desa Dan TPT terhadap Tingkat Kemiskinan Di Wilayah Tapal Kuda - Sari, Beauty Restuning; Asmara, Kiky (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
The Tapal Kuda region recorded the highest poverty rate compared to other areas in East Java from 2020 to 2024. This high poverty level positions poverty as a critical issue requiring serious attention from various stakeholders. Therefore, this research to see the effect of Average Years of Schooling, Village Fund, and Open Unemployment Rate on poverty rates in the Tapal Kuda region. The analysis method used is panel data regression with the Random Effect Model. The results show that Average Years of Schooling has a negative and significant effect, Village Fund has no significant effect, and Open Unemployment Rate has a positive and significant effect on poverty levels in the Tapal Kuda region. The government is advised to expand access to quality education, adjust budget allocation policies to strike a better balance between physical infrastructure development and community empowerment thereby making efforts to reduce poverty more effective and reduce unemployment through the creation of formal jobs, business financing support, and collaboration with companies